Influence of backfilling phase change material on thermal performance of precast high-strength concrete energy pile. (January 2022) - Cao, Ziming; Zhang, Guozhu; Liu, Yiping; Zhao, Xu; Li, Chenglin
Abstract: The use of phase change materials (PCMs) within the precast high-strength concrete (PHC) energy pile is relatively rare. A study concerning the thermal performance of the PHC energy pile backfilled with PCMs were performed to compare with conventional backfill materials. Field tests of the PHC energy pile were conducted. Then, different types of heat transfer numerical models for the PHC energy pile backfilled with water, ordinary grout, and PCMs were established, and the validities of models were confirmed by the field test data and other published studies. The following results are obtained from this study: (1) the thermal performances of the PHC energy pile backfilled with ordinary grout and PCM-type backfill materials (i.e., PCM, enhanced-PCM, and enhanced-PCM-1) are significantly greater than that backfilled with water under continuous operation; (2) intermittent operation has a larger influence on the heat exchange rate of PCM-type backfilled PHC energy pile than ordinary grout backfill material, and enhanced-PCM and enhanced-PCM-1 backfill materials generate higher heat exchange rates for the PHC energy pile than the ordinary grout under intermittent operation; (3) enhancements in the thermal properties of PCMs and intermittent operation both are important to improve the heat transfer performance of the PHC energy pile backfilled with PCMs, and the lower melting temperature of PCMs helps to enhance the thermal performance of PCM-type backfilled PHC energy pile in the cooling mode; and (4) under higher velocity of groundwater flow, ordinary grout backfill material is more suitable for the PHC energy pile compared with PCM-type backfill materials. Highlights: Field thermal response tests of PHC energy pile are carried out. 3D heat transfer numerical model of PCM backfilled PHC energy pile is established. Impact of intermittent operation on heat transfer of PHC energy pile backfilled with PCMs is analyzed. Impact of groundwater on heat transfer of PHC energy pile backfilled with PCMs is assessed.